Combination of high-frequency electrocautery therapy and ALA-PDT in hyperkeratotic vulvar lichen sclerosus: Series of seven cases - Shanshan Ou; Huanli Wang; Weiyu Liu; Huilan Zhu; Wenjun Zhang; Huaping Li; Huiyan Deng (Photodiagnosis and Photodynamic Therapy)
Significance: ALA-PDT effectively treats Vulvar lichen sclerosus et atrophicus (VLSA), but it requires multiple repetitions for satisfactory results. To enhance efficacy, we employed a combination of high-frequency electrocautery therapy and ALA-PDT in treating seven VLSA patients. Approach: Lesions and leukoplakia in the seven women with VLSA were removed using a high-frequency generator. PDT was administered after wound healing, and it was repeated six times. Follow-up assessments were carried out at 1, 3, and 6 months to evaluate the severity of pruritus and investigate lesion repigmentation. Results: Following the combined therapy, the disappearance of pruritus was observed in all patients, and normal color and thickness were restored to their skin. Two patients reported mild pruritus with a score of 2 one month after treatment, which persisted until the 6-month follow-up, while the remaining patients remained free from pruritus. No recurrence of skin lesions was observed in any of the patients. Conclusions: The combined therapy for the treatment of VLSA is found to be convenient, effective, and easily promotable.